The Artistic Marriage between the Word and the Feather in a Diwan "The Pains of Safsafa in Hurricane Seasons" by the poet "Youssef Waghleesi" - Sadika, Maamar (Journal of Human Sciences, 2023)
The combination of poetry and drawing means the ability of both the poet and the painter to transfer his creative experience into an artistic production, where the poet has the talent of making speech in weights and rhythms that are formulated by the ear. Also, the painter has the eye. The association of the written poetic text with drawings is an issue of a difference between a reader who support these forms and symbols, and another reader who rejects this artistic association and does not find any justification, interpretation or function for him to perform. Which makes us wonder whether the contemporary poett "Youssef Waghlissi" succeeded in combining what is linguistic and non-linguistic? Was he smart in this poetic maneuver, and quenched the reader’s thirst with such innovation, or was it a tradition imposed by poetic modernity, and he to submit to this duty? The Diwan was distinguished by the experience of the participation of artists- the caligrapher "Ma’asho Qaroor" and the novelist "Fazila Alfarouq" outside the field of poetry with the poet "Yossef Waghlissi". So, how can different creators create the same work , and give it a distinct form?